COVID-19: Impact on Indian Agriculture - V.D. , Krishnaveni; V. , Harish; P. , Mary Jeyanthi; A. , Mansurali (International Journal of Psychosocial Rehabilitation, 2020)
The COVID-19 infectious disease has brought the world to a social and economic standstill. The number of infected persons has crossed two million and is constantly increasing. Many countries have instituted lockdowns to counter the spread of the infection among the general population. This lockdown has had an impact on every aspect of economic activity. This paper attempts to understand the impact of the lockdown specifically on Indian agriculture and some of its allied sectors. Despite being exempt from the lockdown restrictions, agriculture has been adversely impacted. Dairy, poultry, floriculture, seed production, and several other related industries have been witnessing losses. With the onset of the pandemic in India coinciding with the harvesting for the rabi crop, farmers are struggling with issues like shortages of labor and transport options. The sector is not in a position to absorb the many losses due to a decrease in harvesting, processing, transportation, or demand.